Variations in Adolescent Purpose in Life and Their Association With Lifetime Substance Use. (April 2018) - Abramoski, Kathryn; Pierce, Jennifer; Hauck, Corinne; Stoddard, Sarah
Purpose in life (PIL) promotes positive development and is associated with decreased substance use. However, to our knowledge, researchers have not investigated how different categories of PIL are associated with substance use behavior among youth. Therefore, we sought to explore categories of PIL and how they are related to substance use in a sample of adolescents. Ninth through 12th-grade students from a high school in a Midwest suburban community completed a paper-and-pencil survey ( n = 408, M age = 15.36, SD = 1.21; 50% female; 72% White). Measures included lifetime substance use and categories of PIL. Exploratory factor analyses suggest that there are three categories of PIL. Alcohol and other drug (ATOD) use was inversely related with broad other-promoting PIL, while a broad self-promoting PIL was positively associated with ATOD use. These findings suggest that exploring PIL with students may reduce substance use behavior.